PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR PASSING BAWAH MELALUI PERMAINAN BOLAVOLI MINI (STUDI PADA SISWA KELAS XI IPA I SMAN 2 NGANJUK TAHUN AJARAN 2012-2013) - KANDILA RIANDINI, BETHARI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical Education is one of Education form to use the exercising activity as a facility and an education aim. By the physical educSation, the student can be coached to physical activity belonging to sport skills, one of physical activities is a learning of volley ball low passing match.That's why, it is necessary about the increasing of physical education learning at school, so there is necessary that the implementation about learning method which is able to solve that problem. Based on the problem, the writer classified statement of the problems what the increasing of under pass  result study in match that is done with using cooperative learning method through mini volley ball match in physical education subject at 7th grade